Corrosion and Corrosion Inhibition of High Strength Low Alloy Steel in 2.0 M Sulfuric Acid Solutions by 3-Amino-1,2,3-triazole as a Corrosion Inhibitor - El-Sayed M. Sherif; Adel Taha Abbas; D. Gopi; A. M. El-Shamy (Journal of Chemistry, 2014)
The corrosion and corrosion inhibition of high strength low alloy (HSLA) steel after 10 min and 60 min immersion in 2.0 M H2SO4 solution by 3-amino-1,2,4-triazole (ATA) were reported. Several electrochemical techniques along with scanning electron microscopy (SEM) and energy dispersive X-ray (EDS) were employed. Electrochemical impedance spectroscopy indicated that the increase of immersion time from 10 min to 60 min significantly decreased both the solution and polarization resistance for the steel in the sulfuric acid solution. The increase of immersion time increased the anodic, cathodic, and corrosion currents, while it decreased the polarization resistance as indicated by the potentiodynamic polarization measurements. The addition of 1.0 mM ATA remarkably decreased the corrosion of the steel and this effect was found to increase with increasing its concentration to 5.0 mM. SEM and EDS investigations confirmed that the inhibition of the HSLA steel in the 2.0 M H2SO4 solutions is achieved via the adsorption of the ATA molecules onto the steel protecting its surface from being dissolved easily.